A novel ultra-wide band wearable antenna under different bending conditions for electronic-textile applications. Issue 3 (4th March 2021) - El Gharbi, Mariam; Martinez-Estrada, Marc; Fernández-García, Raul; Ahyoud, Saida; Gil, Ignacio
Abstract: This paper is devoted to a novel textile ultra-wideband (UWB) antenna for wearable applications. The antenna is designed and implemented on a felt textile substrate with attractive features such as a flexible full embroidered topology and a low dielectric loss. In this study, the UWB antenna is evaluated through the reflection coefficient (S11), gain, efficiency and effects of bending. The UWB operation of this compact antenna varies from 3.1 GHz to 11.3 GHz implying a fractional bandwidth of 114%, in which the efficiency is over 60% and the realized gain reaches 4 dB.